Analisis Ergonomi Organisasi Terhadap Kinerja Pegawai Puskesmas Kenali Besar Kota Jambi Tahun 2023 - Purwati, Yunita; Kasim, Felix; Lubis, Basyariah; Aswin, Budi (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2023)
The relationship between organizational ergonomics and performance, namely the organization as a place for employees to carry out work activities can be a pusher or a puller for employees to carry out a task and even become an inhibiting factor for employees to show performance so that it can affect quality and improve performance. This study aims to analyze organizational ergonomics on employee performance at the Community Health Center of Kenali Besar, Jambi City. This type of research is a quantitative study with a cross-sectional research design. The research population was all Community Health Center employees, totaling 41 people who were also used as research samples. Statistical analysis used the chi square or fisher's exact test and logistic regression at the 95% confidence level (p<0.05). The results showed that there was a relationship between communication (p = 0.034), and organizational culture (p = 0.012) with the performance of the Community Health Center of Kenali Besar in Jambi City, while the teamwork variable was not related to employee performance (p = 1.000). The conclusion in this study is that communication and organizational culture have a significant relationship with the performance of the employees at Community Health Center of Kenali Besar, but teamwork has no significant relationship with employee performance. The most dominant variable related to employee performance is organizational culture with a value of B (2.251). The Community Health Center further improves the organizational culture of employees such as always creating innovative ideas at work, dissatisfied with one task so that they are challenged with the next task, work is carried out flexibly, responsively and quickly changes, and the organization must have a clear agreement on the procedures for carrying out the assigned tasks. right and wrong